2018
DOI: 10.1007/s40279-018-0923-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Fundamental Motor Skill Interventions and Physical Activity Levels in Children: A Systematic Review and Meta-analysis

Abstract: There are limited studies measuring both FMS and PA following an FMS intervention, especially in school-aged children. Results indicate that training pre-schoolers at least three times a week in FMS can improve proficiency, increase intensity of PA, and reduce SB, possibly helping to reduce the burden of childhood obesity and its associated health risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
96
2
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 48 publications
8
96
2
12
Order By: Relevance
“…Findings showed that a developmental physical education programme, a therapeutic sensorimotor training and an intensive motor skills training were significantly effective in improving overall FMS among children with ID. These findings were consistent with those found in meta-analyses among youth with TD (Logan et al 2012;Morgan et al 2013;Engel et al 2018). The reviewed interventions were effective when their duration was of 24 weeks, and the training sessions were held three times a week for a duration of 20-30 min.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Findings showed that a developmental physical education programme, a therapeutic sensorimotor training and an intensive motor skills training were significantly effective in improving overall FMS among children with ID. These findings were consistent with those found in meta-analyses among youth with TD (Logan et al 2012;Morgan et al 2013;Engel et al 2018). The reviewed interventions were effective when their duration was of 24 weeks, and the training sessions were held three times a week for a duration of 20-30 min.…”
Section: Discussionsupporting
confidence: 87%
“…; Engel et al . ). The reviewed interventions were effective when their duration was of 24 weeks, and the training sessions were held three times a week for a duration of 20–30 min.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies by De Meester et al [9] and Lubans et al [10] support this hypothesis by showing positive associations between children's level of MC and the time children spent in PA. Motor competence is ideally learned and developed during childhood [11], yet declines in children's MC have been reported over the last years [12,13].According to the concept of physical literacy [14], physical competence (including MC) and engagement in PA are interconnected key elements for the development of active lifestyle patterns. This suggests a reciprocal relationship between MC and PA; children with high MC are more likely to participate in PA than children with low MC, and vice versa [15,16].The impact of the relationship between MC, PA, and SB might be influenced by a set of individual demographic variables. First, children's weight status is recognized as a strong correlate of PA and SB.…”
mentioning
confidence: 99%